Повышение эффективности применения водяных завес при ликвидации последствий чрезвычайных ситуаций, связанных с выбросом опасных химических веществ - Kotov Геннадий; Bulva Александр; Smolyakov А. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The basic method of disinfection and limitation of distribution of cloud of the infected air at liquidation of consequences of emergencies related to the troop landing of hazardous chemical substances is rising of aquatic curtains. However, because of their low absorption activity in relation to many of most widespread hazardous chemical substances, there is the necessity of application of devices providing more effective decline of remaining concentration of toxic matters. The devices (device for cleaning and disinfection of air, wetting impenetrable screen) the use of which individually are described in the article, so combined at liquidation of consequences of emergencies will allow considerably to promote efficiency of the conducted measures. New construction of sleeves nebulizers possessing greater absorption and nebulizing efficiency is also offered.